2015
DOI: 10.1002/pssa.201532324
|View full text |Cite
|
Sign up to set email alerts
|

Substructural investigations, Raman, and FTIR spectroscopies of nanocrystalline ZnO films deposited by pulsed spray pyrolysis

Abstract: Nanocrystalline ZnO films were deposited onto glass substrates in the temperature range of 473-673 K using pulsed spray pyrolysis. The structural, substructural, and optical properties of the films were investigated by means of X-ray diffraction analysis, Raman scattering, and Fourier transform infrared (FTIR) spectroscopy. The effect of the substrate temperature (T s ) on the coherent scattering domain (CSD) sizes L, microstrains e, and microstress s grades, and the average density of dislocations r in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…High −E 2 Low mode at approximately 344 cm −1 and the E 1 (LO) mode at approximately 596 cm −1 , which are similar to previous reports [34,35]. As the doping rate changed, the intensity and position of the E 1 (LO) peak changed slightly.…”
Section: Raman Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…High −E 2 Low mode at approximately 344 cm −1 and the E 1 (LO) mode at approximately 596 cm −1 , which are similar to previous reports [34,35]. As the doping rate changed, the intensity and position of the E 1 (LO) peak changed slightly.…”
Section: Raman Analysissupporting
confidence: 90%
“…As the doping rate changed, the intensity and position of the E 1 (LO) peak changed slightly. Though many previous studies have found that the E 2 High mode is the major peak in hexagonal ZnO [12,16,19,[34][35][36][37][38], we could only observe its trace in the E 2 High −E 2 Low mode.…”
Section: Raman Analysiscontrasting
confidence: 66%
“…Table 1 presents the overview of deposition conditions and precursors typically used to deposit the ZnO, CZTS, and CZT films by spray pyrolysis technique. 7heating plate [18,19].…”
Section: Zno Czts and Czt Thin Films Deposition Methods Peculiaritmentioning
confidence: 99%
“…XRD patterns were normalized to the intensity of the (002) peak of the hexagonal ZnO phase. Phase analysis was performed by comparing interplanar distances and relative intensities of the investigated samples with the standard according to JCPDS 79-0207 [23].…”
Section: Methodsmentioning
confidence: 99%
“…It is known, that ZnO formation method (chemical or physical) has strong effect on the structural-phase state of the samples and the ensemble of the defects [22][23][24], which in turn, determine the structure dependent sensor properties of the material. It can be assumed, that these characteristics also affect the gas sensor properties of ZnO.…”
Section: Introductionmentioning
confidence: 99%